Anti-giardia activity of hexane extract of Citrus aurantifolia (Christim) swingle and some of its constituents - Domínguez Vigil, IG; Camacho Corona, MdR; Heredia Rojas, JA; Vargas Villarreal, Javier; Rodríguez De la Fuente, AO; Heredia Rodríguez, Omar; Mata Cárdenas, BD (African Journals Online, 2015)
Background: Giardia lamblia is a parasite that causes giardiasis in humans and other mammals. The common treatment includes different drugs, which were described to produce unpleasant side effects. Citrus aurantifolia, popularly known as “lima”, is a plant used in traditional medicine to treat gastrointestinal symptoms. The aim of the present study was to evaluate the anti-Giardia activity of 10 pure compounds obtained from a hexanic extract of Mexican lime on the basis of trophozoite growth inhibition. Materials and Methods: A hexanic extract obtained from fresh fruit peels of Citrus aurantifolia was tested on G. lamblia strain 0989:IMSS trophozoites cultured in TYI-S-33 medium. The concentration of all standard drugs, analyzed by gas chromatography, was adjusted at 10 mg/mL. Metronidazole was used as a positive control. Growth inhibition was determined by counting the number of trophozoites using a Neubauer chamber. The 50% inhibitory concentration (IC50) of each drug was calculated by probit analysis and 95% confidence limits were calculated. Results: 4-hexen-3-one, citral and geraniol showed IC50 values of 34.2, 64.5 and 229.49 µg/ml in axenic cultures after 24 hr of incubation, respectively. When these results were compared with a positive control of metronidazole; 4-hexen-3-one was 66 times; citral was 112 and geraniol was 441 times less active respectively. The other tested compounds did not inhibit the growth of cultured G. lamblia trophozoites. Conclusion: The obtained results lead us to propose that these tested compounds from C. aurantifolia have potential for use as therapeutic agents against giardiasis.